Th1/Th2 cytokines in patients with systemic lupus erythematosus: is tumor necrosis factor alpha protective? (2004)
Objectives: To determine the circulating levels of Th1 and Th2 cytokines in patients with systemic lupus erythematosus (SLE) and to elucidate their association with disease activity and autoimmune response. Methods: We included 52 patients and 25 healthy controls. Serum levels of tumor necrosis factor (TNF) , interferon (IFN) , interleukin (IL)-12p70, IL-10, and IL-4, as well as anti-DNA, -Ro, -La, -RNP, and -Sm antibodies were determined by enzyme-linked immunosorbent assay. Disease activity was recorded according to the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and classified as very active (SLEDAI > 13), moderately active (SLEDAI: 3-12), or inactive (SLEDAI < 2). Results: The mean age of the patients was 34.2 12.6 years, and the mean duration of disease was 4.9 7.6 years. Twelve patients (23%), 20 patients (34.5%), and 20 patients (34.5%) had highly, moderately, and inactive SLE, respectively. Levels of IFN-, TNF- , and IL-12 were significantly higher in patients than in healthy controls (P < .03), as well as the IL-12/IL-10, IL-12/IL-4, IFN/IL-10, IFN/IL-4, TNF/IL-10, and TNF/IL-4 ratios (P < .01), suggesting a major participation of Th1 over Th2 cytokines. Nevertheless, a direct correlation between Th1 (IFN- and TNF- ) and Th2 (IL-4 and IL-10) cytokines was observed in patients (r > .5, P < .01), indicating a mutual Th1-Th2 participation. TNF- levels and the TNF/IL-10 ratio were higher in patients with inactive disease compared with patients with very active disease and controls (P < .04). IL-12 levels and IL-12/IL-4, as well as IL-12/IL-10, ratios were higher in patients with very active disease than in those with inactive SLE and controls (P < .01). IL-10 levels were associated with anti-DNA, anti-Ro, and anti-La response (P < .01). Conclusion: Our results suggest that TNF- could be a protective factor in SLE patients, whereas IL-12p70 participates in disease activity and IL-10 influences the autoimmune response (autoantibody production).